A Disturbance in the Force: Cellular Stress Sensing by the Mitochondrial Network - Robert Gilkerson (Antioxidants, 2018)
As a highly dynamic organellar network, mitochondria are maintained as an organellar network by delicately balancing fission and fusion pathways. This homeostatic balance of organellar dynamics is increasingly revealed to play an integral role in sensing cellular stress stimuli. Mitochondrial fission/fusion balance is highly sensitive to perturbations such as loss of bioenergetic function, oxidative stress, and other stimuli, with mechanistic contribution to subsequent cell-wide cascades including inflammation, autophagy, and apoptosis. The overlapping activity with m-AAA protease 1 (OMA1) metallopeptidase, a stress-sensitive modulator of mitochondrial fusion, and dynamin-related protein 1 (DRP1), a regulator of mitochondrial fission, are key factors that shape mitochondrial dynamics in response to various stimuli. As such, OMA1 and DRP1 are critical factors that mediate mitochondrial roles in cellular stress-response signaling. Here, we explore the current understanding and emerging questions in the role of mitochondrial dynamics in sensing cellular stress as a dynamic, responsive organellar network.